The influence of communication and information sources upon decision‐making around complementary and alternative medicine use for back pain among Australian women aged 60–65 years. (6th October 2015) - Murthy, Vijayendra; Adams, Jon; Broom, Alex; Kirby, Emma; Refshauge, Kathryn M.; Sibbritt, David
Abstract: This study examined factors influencing decision‐making on complementary and alternative medicine (CAM) use for back pain and back pain sufferers' communication about CAM use. A cross‐sectional postal survey was conducted in 2011/2012 as a sub‐study of the Australian Longitudinal Study on Women's Health (ALSWH). The sample contained 1620 women from the 1945–1951 cohort of the ALSWH, aged 60–65 years who were eligible for the sub‐study, as they had experienced back pain during 12 months prior to the survey. Of these, 1310 (80.9%) returned completed questionnaires. A significant proportion of women consulted a CAM practitioner (76%, n = 1001) and/or had self‐prescribed CAM treatment (75%, n = 985). Of the women who used CAM for their back pain, 20% consulted their general practitioner (GP) prior to using CAM and 34% always informed their GP following CAM use. Forty‐three per cent of the women were influenced by their doctors, 39% by friends/colleagues, 36% by family/relatives, 33% by their partner, 30% by a CAM practitioner, 20% by a pharmacist, 16% by a book/magazine, 11% by mass media, 10% by an allied health worker and 6% by the Internet. Our results show that information sources used by women for their decision‐making on CAM use differed according to the symptoms. While non‐professional information sources (e.g. family/relatives) positively influenced women in their decision to use CAM for a range of back pain‐related symptoms (e.g. headaches/migraines), doctors and allied health workers (e.g. nurses) negatively influenced women in their decision to consult a CAM practitioner for a range of back pain‐related symptoms (e.g. headaches/migraines, neck pain). Women seek information from a wide range of professional and non‐professional sources with regard to their decision‐making around CAM use for back pain. Back pain care providers need to ensure effective communication with their back pain patients regarding safe, effective and co‐ordinated back pain care options.